Construction of CoSx–ZnIn2S4 hollow nanocages derived from metal–organic frameworks for efficient photocatalytic hydrogen production. (16th July 2021) - Ma, Hongyu; Tan, Yaqi; Liu, Zhifei; Wei, Jianhong; Xiong, Rui
Abstract : CoS x –ZnIn2 S4 heterostructured hollow nanocages exhibit enhanced photocatalytic hydrogen production due to the synergistic effect of unique hollow nanocages and a suitable semiconductor heterostructure. Abstract : Smart heterogeneous structures and rational photocatalyst design play an important role in photocatalytic hydrogen production. In this study, ZnIn2 S4 (ZIS) nanosheets were grown in situ on the surface of CoS x hollow nanocages, derived from ZIF-67 metal–organic frameworks, to obtain hierarchical CoS x /ZnIn2 S4 (CZIS) hollow heterostructured nanocages. The CZIS composites exhibited significant enhanced photocatalytic H2 evolution performance as compared with pure ZIS and CoS x . The optimal content of CoS x was about 30 wt% and the corresponding H2 production rate was 1538.4 μmol g −1 h −1, which was approximately 6.1 times that of the pure ZnIn2 S4 . The improved photocatalytic performance of the CZIS hollow nanocages was attributed to their hollow morphology and well-matched band structure. The hollow structure was favorable to the absorption and utilization of light because of the multiple reflections of light in the cavity. The close surface contact of CoS x and ZnIn2 S4 not only enhanced the carrier separation and inhibited the recombination of photogenerated carriers but it also provided a fast electron transport channel, resulting in significantly improved photocatalytic performance. This study has confirmed that hollow CoS x polyhedra may be a potential alternative to precious metal photocatalytic co-catalysts for the hydrogen generation.